REGRESI POLIARKI DI INDONESIA (2019–2024): ANALISIS DEMOKRASI PROSEDURAL DAN SUBSTANSIAL - KARTIKA DELSYA; RIA ERICA SALTY; RIZKI ANINGRUM (Universitas Sultan Ageng Tirtayasa, 2026)
This study aims to analyze the dynamics of democracy in Indonesia during the 2019–2024 period through the framework of Robert Dahl’s theory of polyarchy. Although Indonesia has procedurally continued to implement electoral democratic mechanisms, various indicators point to significant symptoms of democratic regression. Using a descriptive-analytical qualitative approach based on a literature review, this study examines five key indicators of polyarchy: political participation, contestation, civil liberties, access to information, and democratic institutions. The findings reveal that the quality of polyarchy in Indonesia has undergone substantive degradation due to two main determining factors: the strengthening of legislative oligarchy, which triggers the phenomenon of institutional capture, and the emergence of digital authoritarianism that suppresses civic space through opinion manipulation and the criminalization of expression. The novelty of this research lies in the integration of analysis between capital dominance within law-making institutions and technology-based repression, which simultaneously weakens the oversight function of citizens. The study concludes that Indonesia is currently in a state of “distorted polyarchy,” where democratic instruments are used as a stamp of legitimacy for elite interests. Keywords: Polyarchy, Robert Dahl, Legislative Oligarchy, Digital Authoritarianism, Democratic Regression.